2016
DOI: 10.1021/acsami.6b02522
|View full text |Cite
|
Sign up to set email alerts
|

A Bonded Double-Doped Graphene Nanoribbon Framework for Advanced Electrocatalysis

Abstract: The preparation of a low-cost, high-efficient, and stable electrocatalyst as an alternative to platinum for the oxygen reduction reaction (ORR) is especially important to various energy storage components, such as fuel cells and metal-air batteries. Here, we report a new type of bonded double-doped graphene nanoribbon-based nonprecious metal catalysts in which Fe3C nanoparticles embedded in Fe-N-doped graphene nanoribbon (GNRs) frameworks through a simple pyrolysis. The as-obtained catalyst possesses several d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…With outstanding oxygen reduction reaction (ORR) activity, Pt and alloys catalysts are regarded as the most effective catalysts. Unfortunately, the scarcity and high cost have greatly limited the commercialization of fuel cells [5][6][7][8] . There is no denying that Ptbased catalysts contribute nearly half of the total cost of the fuel cell stacks [6,9] .…”
Section: Introductionmentioning
confidence: 99%
“…With outstanding oxygen reduction reaction (ORR) activity, Pt and alloys catalysts are regarded as the most effective catalysts. Unfortunately, the scarcity and high cost have greatly limited the commercialization of fuel cells [5][6][7][8] . There is no denying that Ptbased catalysts contribute nearly half of the total cost of the fuel cell stacks [6,9] .…”
Section: Introductionmentioning
confidence: 99%
“…The TEM image (Figure b) showed that several black dots with a size of 20–70 nm were embedded in the pristine amorphous carbon after doping with N and trace Fe, which was assigned to the heavy atoms, that is, the Fe moieties in this case . These Fe moieties were confirmed as Fe 3 C, which played a key role for the high activity of the Fe‐doped catalyst. The HRTEM test results revealed that each Fe 3 C nanoparticle was encapsulated by a graphitic carbon shell (with a thickness of 10–20 nm) to form a core–shell structure, as shown in Figure c. An interplanar spacing of 0.401 nm was identified (the top‐right inset of Figure c), which can be assigned to the (110) lattice planes of the Fe 3 C nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The peak located at approximately 26.5° was indexed to the (002) plane of the graphitic carbon (JCPDS No. 41‐1487), which is consistent with the TEM results. The peaks of Fe 3 C were much stronger than those reported in previous studies, which was probably the key reason for the high activity of NFe/CNS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations